Glycine as a signaling molecule and chemoattractant in Trichoplax (Placozoa): insights into the early evolution of neurotransmitters. Issue 6 (8th April 2020) - Romanova, Daria Y.; Heyland, Andreas; Sohn, Dosung; Kohn, Andrea B.; Fasshauer, Dirk; Varoqueaux, Frederique; Moroz, Leonid L.
Abstract : The origin and early evolution of neurotransmitter signaling in animals are unclear due to limited comparative information, primarily about prebilaterian animals. Here, we performed the comparative survey of signal molecules in placozoans – the simplest known free-living animals without canonical synapses, but with complex behaviors. First, using capillary electrophoresis with laser-induced fluorescence detection, we performed microchemical analyses of transmitter candidates in Trichoplax adhaerens – the classical reference species in comparative biology. We showed that the endogenous level of glycine (about 3 mM) was significantly higher than for other candidates such as L-glutamate, L-aspartate, or gamma-aminobutyric acid. Neither serotonin nor dopamine were detected. The absolute glycine concentrations in Trichoplax were even higher than we measured in ctenophores ( Beroe ) and cnidarians ( Aequorea ). We found that at millimolar concentrations of glycine (similar to the endogenous level), induced muscle-like contractions in free behaving animals. But after long incubation (24 h), 10 −3 M of glycine could induce cytotoxicity and cell dissociation. In contrast, micromolar concentrations (10 −5 –10 −4 M) increased Trichoplax ciliated locomotion, suggesting that glycine might act as an endogenous signal molecule. However, we showed than glycine (10 −6 M) can also be a chemoattractant (a guiding factor for food sources), and therefore, act as the exogenous signal. These findings provide an evolutionary base for the origin of transmitters as a result of the interplay between exogenous and endogenous signaling systems early in animal evolution.